Classification of taxes and fees as a method of systematization of environmental taxation in the russian federation - L. S. Samodelko (Вестник университета)
Environmental taxation is an instrument of the state’s tax policy, remaining today one of the vectors of socio-economic development. However, the structural understanding of this mechanism in tax theory has not yet been formed. In this connection, the purpose of this work is to identify, on the basis of the current tax legislation of the Russian Federation, tax tools involved in the regulation of environmental processes. To solve one of the main tasks, namely, to form the theoretical foundations of the algorithm for monitoring and evaluating empirical data within the framework of the state’s tax policy, it is necessary to analyze scientific publications and synthesize knowledge of Russian and foreign practices in the field of environmental taxation. The next task is to formulate conclusions on the further greening of the tax legislation of the Russian Federation. As a result of the conducted research, the author’s approach to the typologization of taxes and fees within the framework of Russian tax legislation is proposed from the position of using the ecological element of fiscal instruments. In the article the ecological element is understood as the socio-economic essence of a particular tax or fee, as well as the presence of an element or a tax mechanism of interaction of an ecological orientation in the payment structure. As a result, it was the elementary analysis of payments that made it possible to identify the range of hypothetically acceptable tax regulators.